Regulasi Emosi Ditinjau Dari Parental Bonding Pada Remaja Pengguna Napza - Usma Yulesa; Rida Yanna Primanita (Happiness: Journal of Psychology and Islamic Science, 2021)
This study aims to see differences in emotional regulation in terms of parental bonding in adolescents using drugs in West Sumatra. Respondents in this study were 40 adolescents using drugs in West Sumatra with an age range of 13-22 years that have high score in parental bonding instrument (PBI). Data collection used the parental bonding instrument (PBI) scale and the emotional regulation scale with the Likert scale model. The data analysis technique used in this research is the one way ANOVA statistical analysis technique. The results showed that there were differences in emotional regulation in terms of parental bonding in adolescents using drugs in West Sumatra with a significance value of 0.007> 0.05. With the empirical mean calculation of 20% in the optimal parenting type, 2.5% in the affectionless control type, 5% of the people in the affectionate constrain type and 72.5% o in the neglected protection type.